PRODUKSI BIOETANOL DARI BIJI BUAH NANGKA (Artocarpus heterophyllus) MELALUI PROSES HIDROLISIS ASAM SULFAT DAN FERMENTASI - Naid, Tadjuddin; Baits, Muzakkir; Triana, Yenni (Fakultas Farmasi UMI, 2012)
FermentationÂ from jackfruit seeds (Artocarpus heterophyllus) through the Process Using Acid Hydrolysis. Bioethanol is ethanol fermentation process biomass results with the help of microorganisms. Raw materials for bioethanol is sugary materials, starchy and fibrous. This study triesÂ to make bioethanol from jackfruit seeds (Artocarpus heterophyllus) which is a starchy material. during these jackfruit seeds into consumption only partly public and partly not used. The purpose of this study was to determine the optimum concentration of H2SO4on the hydrolysis process and determine the optimum fermentation time in the fermentation process. The process of making ethanol in two steps, namely acid hydrolysis and fermentation. Cassava peel hydrolyzed by using a solution of H2SO4 in a variety of variable concentrations (0.1, 0.5 and 1 M) at a temperature of 100oC for 1 hour. Then a solution of the hydrolysis fermented with various variables days (1, 2, 3, 4, 5, 6 and 7 days). The result showed that the optimum concentration of H2SO4 solution for the hydrolysis reaction is 1 M at a temperature of 100oC for 1 hour and the optimum fermentation time in the fermentation process is on day 4 where the produced ethanol at 13,19% v/v.Â Key words : Fermentation, Artocarpus heterophyllus, Hydrolysis